Directional Weak Intermolecular Interactions: sigma-Hole Bonding - Murray, Jane S.; Riley, Kevin E.; Politzer, Peter; Clark, Timothy (Australian Journal of Chemistry, 2010)
The prototypical directional weak interactions, hydrogen bonding and sigma-hole bonding (including the special case of halogen bonding) are reviewed in a united picture that depends on the anisotropic nature of the molecular electrostatic potential around the donor atom. Qualitative descriptions of the effects that lead to these anisotropic distributions are given and examples of the importance of sigma-hole bonding in crystal engineering and biological systems are discussed.